Housing Supply and Housing Quality of Low Income Households. Challenges, Options and Limitations of Housing Policy and Urban Development using the Example of Sonnenberg Neighbourhood in Chemnitz - Brinker, Dörthe; Sinning, Heidi (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
In Germany, social disparities between the rich and the poor, and the poverty risk have been continuously increasing in recent years, in particular with regard to single parents, people with low income and increasingly also the elderly. This dilemma is not only a challenge to society in general but also a huge challenge for cities and communities. In addition, the problem is intensified by a tight housing market, characterized by a lack of housing for low-income households. Morever, affordable and demand-oriented housing is becoming scarcer due to segregation and gentrification. A wide array of strategies has been developed to tackle these problems, e.g. rent control and new ways of providing public land for housing, to secure an appropriate supply of quality housing for low income households. Against this background the paper deals with two selected strategic approaches, namely cooperation of housing industry and urban development, and integrated area development. The case study of the Sonnenberg neighborhood in Chemnitz exemplarily describes options and limitations of housing supply. The results are discussed with regard to scientific debates on cooperative and socially cohesive urban development policies.
Keywords: Housing policy; Housing provision; Quality of housing conditions; Low-income households; Housing associations; Urban development